Innovative Approaches and Comprehensive Strategies in the Treatment of Acne Vulgaris. A Multi Faceted Review - Maj, Adrian; Warno, Martyna (Quality in Sport, 2024)
Introduction Acne vulgaris, widely recognized as one of the most prevalent skin disorders, presents numerous diagnostic and therapeutic challenges. It affects not only adolescents during puberty but also adults, constituting a multifaceted phenomenon that influences both the physical condition of the skin and the psychological well-being of individuals. Acne’s impact extends to overall well-being and social life. Given the complexity of this condition, a thorough understanding of its etiologies and the pursuit of effective therapeutic methods are essential. This review aims to evaluate fractional laser therapy as a potentially effective and safe treatment for acne vulgaris, emphasizing its potential to improve the quality of life and comfort for individuals suffering from this condition. Aim of the Study The objective of this review is to delineate the causes of common acne occurrence and explore solutions in its treatment process. The primary aim is to present fractional laser therapy as an effective treatment modality for acne vulgaris. Material and Method This article synthesizes the current state of knowledge regarding acne vulgaris, drawing on various scientific articles. Conclusions The path to eliminating skin lesions necessitates a multifaceted and holistic approach, with essential guidance from a dermatologist. Effective acne treatment requires an individualized strategy that considers multiple factors. In practice, a combination of different treatment modalities often yields the best results.